Work-related use of information and communication technologies after hours (W_ICTs) and emotional exhaustion: A mediated moderation model. (February 2018) - Xie, Julan; Ma, Hongyu; Zhou, Zhiqing E.; Tang, Hanying
Abstract: Work-related use of information and communication technologies after hours (W_ICTs) has been found to have an extensive and profound influence on employees' work and family lives. In the current study, we examined the effect of W_ICTs on employee emotional exhaustion and investigated the underlying mechanism with two different samples. In Study 1, data from 447 Chinese college counselors showed that W_ICTs was positively associated with emotional exhaustion, but this positive relationship was weaker for individuals with higher work-home integration preference. These findings were replicated in Study 2, using a sample of 340 full-time employees from different companies in different industries in China. Further analyses showed that work schedule and location control mediated the moderating effect of work-home integration preference on the relationship between W_ICTs and emotional exhaustion. These findings provide strong support for the proposed mediated moderation model, and demonstrate the importance of adopting a needs-supplies fit perspective to understanding the influence of W_ICTs. Highlights: Work-Related use of ICTs after hours (W_ICTs) is common in China. W_ICTs is a risk factor of emotional exhaustion for Chinese employees. Preference to integrate work and family roles attenuates the inducing effect. Work schedule and location control is a key mediator of this moderation effect.